Role of MMP-1 (-519A/G, -1607 1G/2G), MMP-3 (Lys45Glu), MMP-7 (-181A/G), and MMP-12 (-82A/G) Variants and Plasma MMP Levels on Obesity-Related Phenotypes and Microvascular Reactivity in a Tunisian Population. (26th November 2017) - Boumiza, Soumaya; Bchir, Sarra; ben Nasr, Hela; Abbassi, Ammar; Jacob, Marie-Paule; Norel, Xavier; Tabka, Zouhair; Chahed, Karim
Abstract : Aims . The impact of MMP-1 (-519A/G, -1607 1G/2G), MMP-3 Lys45Glu (A/G), MMP-7 -181A/G, and MMP-12 -82A/G variants and plasma MMP levels on obesity and microvascular reactivity in Tunisians. Methods . Our population included 202 nonobese and 168 obese subjects. Anthropometric, biochemical, and microvascular parameters were determined according to standard protocols. PCR-RFLP and ELISA were used to determine the genetic variants and levels of MMPs, respectively. Results . The MMP-3 45Glu (G) allele associates with higher anthropometric values and MMP-3 levels compared to AA genotype carriers (BMI (kg/m 2 ): 30 ± 0.51 versus 27.33 ± 0.8, P = 0.004 ; MMP-3 levels: 7.45 (4.77–11.91) versus 5.21 (3.60–10.21) ng/ml, P = 0.006 ). The MMP-12 -82G allele was also associated with higher BMI values when compared to subjects carrying the AA genotype (31.41 ± 0.85 versus 28.76 ± 0.43, P < 0.001 ). Individuals carrying the MMP-3 45G or MMP-12 -82G variants were also associated with a higher risk for severe forms of obesity (MMP-3: OR = 1.9, P = 0.002 ; MMP-12: OR = 2.63, P = 0.003 ). Similarly, the MMP-7 -181G allele was associated with a higher MMP-7 level and an increased risk for morbid obesity when compared to AA genotype carriers (0.32 (0.31–0.60) versus 0.18 (0.17–0.24) ng/ml, P = 0.01 ; OR = 1.67, P = 0.02, resp.). Conclusion . MMP-3, MMP-7, and MMP-12 polymorphisms associate with obesity risk and its severity.